Kemampuan Penerapan Aturan Tata Bahasa Dalam Penulisan Bahasa Arab - Emiyiati, Rifka; Amaliah, Rizaktul; Alfayed, Muhammad; Umair, Muhammad; Nasution, Sahkholid (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Arabic language learning in Islamic educational institutions in Indonesia, especially in madrasahs, faces challenges primarily stemming from teacher weaknesses, suboptimal curricula, and often unsystematic materials. It is crucial to develop integrated learning materials that focus on grammar, consider difficulty levels, and provide practical exercises to enhance interest and learning outcomes. Efforts to improve the quality of Arabic language education should concentrate on teacher training to boost competence. Additionally, curriculum revisions, emphasizing the development of materials aligned with learners' needs, can be a strategic step. Ensuring active student involvement by creating engaging materials that follow challenging yet accessible learning principles is also essential. With these steps, it is anticipated that Arabic language learning in madrasahs will undergo significant positive changes.